Impact of Environmental Degradation on Human Health: An Assessment Using Multicriteria Decision Making - Mumtaz, Ayesha; Rehman, Erum; Rehman, Shazia; Hussain, Iftikhar (Frontiers in Public Health, 2022)
Air pollution has emerged as a major global concern in recent decades as a result of rapid urbanization and industrialization, leading to a variety of adverse health outcomes This research aims to investigate the influence of exposure to ambient and household particulate matter pollution (PM2.5), and ground-level ozone (O3) pollution on respiratory and cardiac mortality in Pakistan. We used grey incidence analysis (GIA) methodology to estimate the degree of proximity among selected variables and rank them based on mortality. Hurwicz’s criterion is then adopted for further optimization by prioritizing the selected factors with the greatest influence on respiratory and cardiac mortality. The GIA findings revealed that asthma mortality is considerably impacted by exposure to ambient and household PM2.5 concentration while ischemic heart disease (IHD) mortality is potentially influenced by ground-level ozone exposure. Furthermore, results based on Hurwicz’s analysis demonstrated that exposure to ambient PM2.5 concentration appeared as the most intensified factor of respiratory and cardiac mortality. This corroboration adds to the growing body of research demonstrating that exposure to ambient PM2.5 adversely leads to respiratory and cardiac risks, emphasizing the demand for further air quality improvement in Pakistan. Besides, the suggested methodologies provide a valuable tool and additional practical knowledge for policymakers and decision-makers in drawing rational decisions.